Determinants of contraceptive method preferences and satisfaction among patients visiting to a post-partum center: A cross-sectional study - Latika; Himanshi Sidana; Pushpa Dahiya (Asian Journal of Medical Sciences, 2025)
Background: Women’s health and well-being are intricately linked to family planning services, yet obstacles remain in the effective use of contraceptives despite widespread awareness.